Glycated hemoglobin levels and risk of all-cause and cause-specific mortality in hemodialysis patients with diabetes. (August 2022) - Kim, Dae Kyu; Ko, Gang Jee; Choi, Yun Jin; Jeong, Kyung Hwan; Moon, Ju Young; Lee, Sang Ho; Hwang, Hyeon Seok
Abstract: Aim: Adequate glycemic control is fundamental for improving clinical outcomes in hemodialysis patients with diabetes. However, the target for glycated hemoglobin (HbA1c) level and whether cause-specific mortality differs based on HbA1c levels remain unclear. Methods: A total of 24, 243 HD patients with diabetes were enrolled from a multicenter, nationwide registry. We examined the association between HbA1c levels and the risk of all-cause and cause-specific mortality. Results: Compared to patients with HbA1c 6.5%–7.5%, patients with HbA1c 8.5–9.5% and ≥9.5% were associated with a 1.26-fold (95% CI, 1.12–1.42) and 1.56-fold (95% CI, 1.37–1.77) risk for all-cause mortality. The risk of all-cause mortality did not increase in patients with HbA1c < 5.5%. In cause-specific mortality, the risk of cardiovascular deaths significantly increased from small increase of HbA1c levels. However, the risk of other causes of death increased only in patients with HbA1c > 9.5%. The slope of HR increase with increasing HbA1c levels was significantly faster for cardiovascular causes than for other causes. Conclusions: There was a linear relationship between HbA1c levels and risk of all-cause mortality in hemodialysis patients, and the risk of cardiovascular death increased earlier and more rapidly, with increasing HbA1c levels, compared with other causes of death.